2005
DOI: 10.1080/07399330590885803
|View full text |Cite
|
Sign up to set email alerts
|

Donkey Work: Women, Religion, and HIV/AIDS in Malawi

Abstract: Addressed in this article are the familial, cultural and religious influences on Malawi women that contribute to HIV/AIDS. Thirty-nine adult Malawi women representing voluntary assistance groups, religious groups, and university women participated in 3 focus groups in Malawi. Interview data were taped, transcribed, and analyzed using qualitative descriptive analysis. Findings revealed that multiple burdens in the lives of Malawi women resulting from poverty and responsibility for family members are made more o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In essence, having an education cannot be interpreted as having significant knowledge of HIV and its transmission. However, other studies have found a protective effect of a higher education level [36,62,64,65].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In essence, having an education cannot be interpreted as having significant knowledge of HIV and its transmission. However, other studies have found a protective effect of a higher education level [36,62,64,65].…”
Section: Discussionmentioning
confidence: 83%
“…HIV is of increasing concern in women in Africa [36,37] and it could also be worse for women immigrants than for male immigrants [6,37]. Women face a range of HIV-related risk factors and vulnerabilities that men and boys do not, many of which are embedded in the social relations and economic realities of their societies [36,[38][39][40][41][42][43][44]. The vulnerability of women and girls to HIV infection stems not simply from ignorance, but from their pervasive disempowerment [36,[38][39][40][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of "burden," or what we have termed "challenges," as being central to the lives of women in Malawi was identified by Rankin, Lindgren, Rankin, and Ng'oma (2005) in their study of the familial, cultural, and religious influences that contribute to HIV infection. These researchers identified poverty and lack of formal education as contributing factors to women's burden.…”
Section: Discussionmentioning
confidence: 99%
“…In another study carried out in Southern Africa among Anglican Churches, fewer than 10 percent of the respondents agreed or partly agreed that PLWHA were not good Christians (HSRC, 2006). Rankin et al (2005) also in their work in Eastern and Southern Africa reported that many Christians and Moslems believe that living with HIV/AIDS implies promiscuous or sinful behaviours. There is therefore the attitude that PLWHA deserve their plight because they did not take precaution.…”
Section: Level Of Educationmentioning
confidence: 99%